PROFESIONALITAS GURU ILMU PENGETAHUAN SOSIAL (IPS) DI SEKOLAH DASAR - I.ketutp.artana, (Pendidikan Dasar, 2012)
Abstract:This research aims at describing teacher abilities in making instructional planning, implementing, evaluating, in building personal relationship and factors influencing their skills to conduct the teaching-learning process of social science in primary schools. The data needed are obtained through interview, documentation and IPKG and are directly analysed in the field. The results show that abilities to plan and implement are fair and are good for building personal relationship. Being professional and creative greatly influence the teaching-learning process. Abstrak:Penelitian ini untuk mengkaji kemampuan guru SD lakarsntri dalam kemampuan pembelajaran IPS meliputi perencanaan, pelaksanaan, evaluasi, dan hubungan antar pribadi, serta factor yang mempengaruh keterampilan guru dalam KBM.  Interviu, dokumentasi dan IPKG digunakan sebagai pengumpulan data. Data dianalisis pada saat dilapangan. Hasil penelitian adalah kemampuan guru SD membuat perencanaan kategori cukup, pelaksanaan KBM kategoricukup evaluasi dan hubungan antar pribadi baik, serta profesionalitas  dan kreatifitas mempengaruhi kemampuan guru dalam KBM.